MSME lending and its impact on the unemployment rate: Evidence from Indonesia - Ulya MahaPutri, Ummi Khalida; Satrianto, Alpon (Optimum: Jurnal Ekonomi dan Pembangunan, 2024)
Micro, small, and medium enterprises (MSMEs) are business sectors that contribute positively to economic development and their contribution to national income. However, as the number of MSMEs increases but MSME faces several problems. The most prominent issue is the lack of capital owned by the entrepreneurs to develop their businesses. In lending, there are several things that need to be considered by creditors and debtors to maintain the intermediary function of the bank. By providing targeted credit, more workers can be absorbed so that Indonesia's unemployment rate continues to fall. This study using panel data regression. First model  using the random effect model (REM) method and second model  using the fixed effect model (FEM) method with a cross-section of 33 provinces in Indonesia and time series 2015-2022. The test results show that the DPK variable, the number of branches, and inflation have a positive and significant effect on total MSME lending and the NPL variable has no effect on total MSME credit. Furthermore, the total MSME lending variable and the economic growth rate have a negative significant effect on the unemployment rate. This research provides a deeper understanding of the factors that determine MSME lending and how they relate to the unemployment rate in 33 Indonesian provinces. It can also be used as a basis for formulating more effective policies related to MSME lending with the potential to reduce the unemployment rate.